Assessing appendicular skeletal muscle mass with bioelectrical impedance analysis in free-living Caucasian older adults. Issue 4 (August 2015) - Sergi, Giuseppe; De Rui, Marina; Veronese, Nicola; Bolzetta, Francesco; Berton, Linda; Carraro, Sara; Bano, Giulia; Coin, Alessandra; Manzato, Enzo; Perissinotto, Egle
Summary Background & aims Aging is characterized by a loss of appendicular skeletal muscle mass (ASMM) leading to physical disability and death. Bioelectrical impedance analysis (BIA) is reliable in estimating ASMM but no prediction equations are available for elderly Caucasian subjects. The aim of the study was to develop and validate an equation derived from bioelectrical impedance analysis (BIA) to predict appendicular skeletal muscle mass (ASMM) in healthy Caucasian elderly subjects, taking dual X-ray absorptiometry (DXA) as the reference method, and comparing the reliability of the new equation with another BIA-based model developed by Kyle et al. (Kyle UG, Genton L, Hans D, Pichard C, 2003). Methods With a cross-sectional design, 296 free-living, healthy Caucasian subjects (117 men, 179 women) over 60 years of age were enrolled. Lean mass of limbs was measured with DXA to ascertain ASMM (ASMMDxA). Whole-body tetrapolar BIA was performed to measure resistance (Rz), resistance normalized for stature (RI), and reactance (Xc). The BIA multiple regression equation for predicting ASMM was developed using a double cross-validation technique. The predicted ASMM values were compared with ASMMKyle, i.e. ASMM estimates derived from the model developed by Kyle et al. (Kyle et al., 2003). Results Cross-validation resulted in a unique equation using the whole sample: ASMM (kg) = −3.964 + (0.227*RI) + (0.095*weight) + (1.384*sex) + (0.064*Xc) [R2 = 0.92 and SEE = 1.14 kg]. In our sample, ASMMKyle differed significantly from the ASMMDxA (p < 0.0001), with a mean error of −0.97 ± 1.34 kg (5.1 ± 6.9%). Unlike the present BIA prediction equation, the Kyle et al. model showed a correlation between the bias and the mean of ASMMDxA and ASMMKyle (r = −0.406, p < 0.001). Conclusion The new BIA equation provides a valid estimate of ASMM in older Caucasian adults.